2021
DOI: 10.6023/cjoc202102039
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Iodide-Triphenylphosphine-Mediated Photoredox Alkylation of Aldimines

Abstract: The photoredox reactions involving electron donor-acceptor (EDA) complexes have attracted significant attentions in the last decade. Very recently, the sodium iodide-triphenylphosphine-N-acyloxyphthalimide EDA complex has been discovered and employed in developing several net redox-neutral photoreactions. Herein, the EDA complex has been applied in a net reductive setup for the first time to establish a photoredox alkylation of aldimines without photosensitizer. The reaction affords not only high yields for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…During our previous work, 14 we noticed that an orange colour appeared upon mixing NHPI esters and DIPEA in methylene chloride (DCM). Further study confirmed the formation of an EDA complex between NHPI esters and DIPEA.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…During our previous work, 14 we noticed that an orange colour appeared upon mixing NHPI esters and DIPEA in methylene chloride (DCM). Further study confirmed the formation of an EDA complex between NHPI esters and DIPEA.…”
Section: Resultsmentioning
confidence: 97%
“…In the screening of alkali metal carbonates, Na 2 CO 3 was found to be less effective (entry 11), and no reaction took place with K CO 3 and Cs 2 CO 3 (entries 12 and 13). Significantly improved results were obtained in the reactions under violet light (entries [14][15][16][17]. The reactions proceeded significantly faster (taking ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, Shen and colleagues made a notable contribution by disclosing a NaI/PPh 3 EDA complex-mediated photoredox alkylation of aldimines 20 ( Scheme 11 ) [ 20 ]. This newly developed method offered a reliable and efficient route for the synthesis of unnatural amino acids and amines.…”
Section: Reviewmentioning
confidence: 99%